Boswellia serrata Extract, 5-Loxin®, Prevents Joint Pain and Cartilage Degeneration in a Rat Model of Osteoarthritis through Inhibition of Inflammatory Responses and Restoration of Matrix Homeostasis. (19th October 2022) - Shin, Mi-Rae; Kim, Hwa-Young; Choi, Hwang-Yong; Park, Kyoung Sik; Choi, Hak Joo; Roh, Seong-Soo
Abstract : Osteoarthritis (OA) is a chronic, progressive joint disease associated with pain, functional impairment, and diminished quality of life in affected individuals. At a societal level, it also has a high economic burden. Boswellia serrata has been reported to have potent anti-inflammatory, antiarthritic, and analgesic effects. The aim of this study was to explore the therapeutic potential and possible underlying mechanism of 5-Loxin®, a standardized Boswellia serrata extract, in a rat model of OA. The OA model was established by the intra-articular injection of 50 μ L of monosodium iodoacetate (MIA) (60 mg/mL). 5-Loxin® was administered orally, and efficacy was evaluated through serum analysis, real-time polymerase chain reaction (PCR), histologic staining, and micro-computed tomography (micro-CT). Results indicated that administration of 5-Loxin® can relieve OA joint pain through inhibition of both inflammatory processes and cartilage degeneration. In the group of rats treated with 5-Loxin®, the suppression of inflammatory enzymes such as cyclooxygenase (COX)-2 and 5-lipoxygenase (LOX) resulted in a significant reduction in the prostaglandin (PG) E2 and leukotriene (LT) B4 levels. Moreover, 5-Loxin® ameliorated the deterioration of the main components of the articular extracellular matrix (ECM), such as glycosaminoglycans (GAGs) and aggrecan, through the downregulation of matrix metalloproteinases (MMPs). These findings suggest that 5-Loxin® may be a potential therapeutic agent for the treatment of OA.